2022
DOI: 10.1097/icb.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Clostridial Endophthalmitis: Clinical Presentations, Management Outcomes, and Review of Literature

Abstract: Purpose: To describe the clinical presentations, diagnosis and management outcomes of clostridial endophthalmitis, and a review of the previous literature.Design: Retrospective, interventional case series from January 2005 to March 2018 and a literature review.Methods: The study included seven eyes of seven patients with culture-proven Clostridium sp. endophthalmitis. Identification of Clostridium sp. was confirmed by the VITEK 2 system using the ANC card. When VITEK failed to identify the organism, MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Early administration of vitrectomy can save patient vision (to a certain extent) and preserve the eyeball. 13…”
Section: Discussionmentioning
confidence: 99%
“…Early administration of vitrectomy can save patient vision (to a certain extent) and preserve the eyeball. 13…”
Section: Discussionmentioning
confidence: 99%
“…Clostridial ocular infections have been well documented in humans 6 in association with perforating eye injury resulting in panophthalmitis 7 . However, none of the human case reports nor studies in animals have reported the isolation of C. chauvoei from ocular lesions.…”
Section: Introductionmentioning
confidence: 99%